Effect of biofertilizers on yield and quality properties of wheat ( Triticum aestivium L.): خميس حبيب مطلك - Mutlag, Khamees Habeeb; Mshemish, Nagaam Abdulrazaq; AL – Kinany, Fadhel S.; Mohammad, Khlood Abd – Alelah; Abdulrahem, Safaa; Abdulwahab, Hazim Jasim; Mahdi, Issa Saleh; Mohamad, Mostafa Talib (Journal of Kerbala for Agricultural Sciences, 2018)
Field experiment at the agricultural research directorate / Ministry of science and technology was conducted using CRD design with different combinations of biofertilizers of Rhizobium spp. and Azospirillum brasilense with 50 of chemical fertilizers for wheat to reduce chemical fertilization which are costly and create environmental proplems. Four treatments of the combinations of bacteria and treatment of control )100% chemical fertilization( were used. Results showed that the best treatment of biofertilizer was the combination of Azospirillum brasilense and Rhizobium leguminosarum RL2 ( Az. + RL2 ) recorded plant height ( 90.6 cm ) spike no.( 362.6 / m² ) comparing with control treatment ( 100 % chemical fertilization ) which gave 87.8 cm and 357.1 /m² respectively .In the same manner yield results showed that the same treatment improved yield to 4.42 ton .hr-1 comparing with control which gave 4.34 ton. hr-1. Results showed also that the combination of Az.+RL2 was the best treatment for enhancing wheat quality parameters recorded such as protein 12.84 % , ash 0.67% and dry glutein 9.44 % in comparison with the control ( 100% chemical fertilization) which were 11.76 % , 0.52 % ,9.39 % respectvelly.